Impact of metoprolol treatment on mental status of chronic heart failure patients with neuropsychiatric disorders - Liu X; Lou X; Cheng X; Meng Y (Dove Medical Press, 2017)
Xuelu Liu,1 Xueming Lou,1 Xianliang Cheng,2 Yong Meng1 1Department of Cardiology, 2Department of Endocrinology, The Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People’s Republic of China Background: Metoprolol treatment is well established for chronic heart failure (CHF) patients, but the central nervous system side effects are often a potential drawback.Objective: To investigate the impact of metoprolol treatment on change in mental status of CHF patients with clinical psychological disorders (such as depression, anxiety, and burnout syndrome).Methods: From February 2013 to April 2016, CHF patients with clinical mental disorders received metoprolol (23.75 or 47.5 mg, qd PO, dose escalated with 23.75 mg each time until target heart rate [HR] <70 bpm was achieved) at the Second Affiliated Hospital of Kunming Medical University. Mental status was assessed by means of the Hospital Anxiety and Depression Scale (HADS) and the Copenhagen Burnout Inventory (CBI) scale. The primary outcome assessed was change in mental status of patients post-metoprolol treatment and the association with reduction in HR achieved by metoprolol.Results: A total of 154 patients (median age: 66.39 years; males: n=101) were divided into eight groups on the basis of their mental status. HR decreased significantly from baseline values in all the groups to <70 bpm in the 12th month, P≤0.0001. The HADS depression and CBI scores significantly increased from baseline throughout the study frame (P≤0.0001 for all groups), but a significant decrease in the HADS anxiety score was observed in patients with anxiety (P≤0.0001 for all groups). Regression analysis revealed no significant correlation in any of the groups between the HR reduction and the change in the HADS/CBI scores, except for a change in the CBI scores of CHF patients with depression (P=0.01), which was HR dependent.Conclusion: Metoprolol treatment worsens the depressive and high burnout symptoms, but affords anxiolytic benefits independent of HR reduction in CHF patients with clinical mental disorders. Hence, physicians need to be vigilant while prescribing metoprolol in CHF patients who present with mental disorders. Keywords: metoprolol, chronic heart failure, HADS anxiety and depression, high burnout, CBI scale, heart rate